Understanding Charge Transport in High‐Mobility p‐Doped Multicomponent Blend Organic Transistors. (11th September 2020) - Scaccabarozzi, Alberto D.; Scuratti, Francesca; Barker, Alex J.; Basu, Aniruddha; Paterson, Alexandra F.; Fei, Zhuping; Solomeshch, Olga; Petrozza, Annamaria; Tessler, Nir; Heeney, Martin; Anthopoulos, Thomas D.; Caironi, Mario
Abstract: The use of ternary systems comprising polymers, small molecules, and molecular dopants represents a promising approach for the development of high‐mobility, solution‐processed organic transistors. However, the current understanding of the charge transport in these complex systems, and particularly the role of molecular doping, is rather limited. Here, the role of the individual components in enhancing hole transport in the best‐performing ternary blend systems comprising the small molecule 2, 7‐dioctyl[1]benzothieno[3, 2‐ b ][1]benzothiophene (C8 ‐BTBT), the conjugated polymer indacenodithiophene‐ alt ‐benzothiadiazole (C16 IDT‐BT), and the molecular p ‐type dopant (C60 F48 ) is investigated. Temperature‐dependent charge transport measurements reveal different charge transport regimes depending on the blend composition, crossing from a thermally activated to a band‐like behavior. Using the charge‐modulation spectroscopy technique, it is shown that in the case of the pristine blend, holes relax onto the conjugated polymer phase where shallow traps dominate carrier transport. Addition of a small amount of C60 F48 deactivates those shallow traps allowing for a higher degree of hole delocalization within the highly crystalline C8 ‐BTBT domains located on the upper surface of the blend film. Such synergistic effect of a highly ordered C8 ‐BTBT phase, a polymer bridging grain boundaries, and p ‐doping results in the exceptionally high hole mobilities and band‐like transport observed in this blend system. Abstract : In this work, the charge transport of the best‐in‐class solution processed organic field‐effect transistor is investigated. The device is based on a blend of small molecule and polymer, with the addition of a molecular dopant, resulting in exceptionally high charge hole mobilities. By combining different electro‐optical characterization techniques, the synergistic interactions between the different components and a band‐like transport are revealed.